2015
DOI: 10.2172/1234791
|View full text |Cite
|
Sign up to set email alerts
|

Energy Savings Potential of Radiative Cooling Technologies

Abstract: EnergyPlus does not support the specification of rooftop radiative heat exchangers, so custom heat transfer modeling was applied to simulate the flows of heat between the heat exchanger, building, and sky, and the anticipated hydronic loop conditions were passed back into the EnergyPlus model. This custom modeling was performed in EnergyPlus's energy management system (EMS) framework, which allows the user to build equations that overwrite certain predetermined points of intervention in the EnergyPlus model. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Passive cooling requires no electricity and thus provides opportunities to solve problems associated with the energy crisis . Recently developed concepts in photonic designs, nanomaterials, and manufacturing approaches have opened up the possibilities for passive radiative coolers that function in the daytime, which can afford exceptional levels of energy savings .…”
mentioning
confidence: 99%
“…Passive cooling requires no electricity and thus provides opportunities to solve problems associated with the energy crisis . Recently developed concepts in photonic designs, nanomaterials, and manufacturing approaches have opened up the possibilities for passive radiative coolers that function in the daytime, which can afford exceptional levels of energy savings .…”
mentioning
confidence: 99%
“…Several studies demonstrated that photonic-based radiative coolers offer an important potential to reduce the cooling demand of buildings. In [33], it is estimated that a hybrid photonic cooling structure can save about 118 MWh per year in Phoenix AZ, while in [97], it is estimated that a similar photonic radiative cooling system can save up to 103 MWh electricity in Miami, 55 MWh in Las Vegas, 50 MWh in Los Angeles, 24 MWh in San Francisco and 43 MWh in Chicago, per year. This corresponds to about 50%, 45%, 65%, 68%, and 55% of the electricity consumed by a Variable Air Volume system in the above five cities respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Equations (8, 9), T sky , T clear sky and T outd are in K. In hot climates, to maximize the amount of heat transfer by radiation from the outdoor surface to the sky, and hence decreasing the cooling load of buildings, the long-wave emissivity of the outdoor surfaces, ε Ls , should be high. With the new technology of reflective materials and radiative cooling materials, their long-wave emissivity are maximized to be close to 1.0 so as to be able to emit the surface's thermal energy through the sky (Catalanotti et al, 1975;Fernandez et al, 2015;Kubota, 2017;Knoss, 2018).…”
Section: Boundary Conditionsmentioning
confidence: 99%